The Development of Problem Solving To Improve Understand Mathematical Concepts - Irin Irawati Sirait; Haninda Bharata; Asmiati Asmiati (SAINTIS Publishing, 2020)
This study aims to 1) develop a problem solving learning model that is oriented towards the ability to understand mathematical concepts, 2) test the feasibility of a model developed on algebraic function derived material, and 3) test the effectiveness of the product of development. This study refers to the Research and Development procedure of Borg and Gall which is simplified into six stages and the resulting product is refined with ASSURE learning design theory. Data were analyzed with qualitative descriptive methods and cognitive learning outcomes with normalized N-gain to determine the effectiveness of the model, Independent t-test to determine differences in learning outcomes. The results were obtained through tests of mathematical concept understanding ability. The results showed that 1) the development of the learning model was carried out with due regard to the components of the model, 2) the results of the development of the learning model were feasible to be applied to the material derived from algebraic functions, 3) the developed learning model was able to improve the ability to understand mathematical concepts. The results of the study can be concluded that the problem solving learning model oriented on the ability to understand mathematical concepts is more effective than conventional learning models.